2001
DOI: 10.1051/0004-6361:20010317
|View full text |Cite
|
Sign up to set email alerts
|

The M 31 double nucleus probed with OASIS and HST

Abstract: Abstract. We present observations with the adaptive optics assisted integral field spectrograph OASIS of the M 31 double nucleus in the spectral domain around the Calcium triplet at a spatial resolution better than 0. 5 F W HM. These data are used to derive the two-dimensional stellar kinematics within the central 2 . Archival WFPC2/HST images in the F300W, F555W and F814W bands are revisited to perform a photometric decomposition of the nuclear region. We also present STIS/HST kinematics obtained from the arc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
107
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 32 publications
12
107
0
4
Order By: Relevance
“…We find that m=1 mode instability is present in certain stellar disks harboring a SBH, which is not fixed, as long as we have Mass SBH /M ass disk 2.0. This mass range condition for the SBH is in accordance with recent numerical works (Bacon et al 2001, Jacobs & Sellwood 2001, Salow & Statler 2001. Our models also show that there is a strong correlation between the m=1 perturbation and the central mass displacement, suggesting a similar mechanism as the eccentric instability studied by other authors (Adams et al 1989, Taga & Iye 1998.…”
supporting
confidence: 92%
“…We find that m=1 mode instability is present in certain stellar disks harboring a SBH, which is not fixed, as long as we have Mass SBH /M ass disk 2.0. This mass range condition for the SBH is in accordance with recent numerical works (Bacon et al 2001, Jacobs & Sellwood 2001, Salow & Statler 2001. Our models also show that there is a strong correlation between the m=1 perturbation and the central mass displacement, suggesting a similar mechanism as the eccentric instability studied by other authors (Adams et al 1989, Taga & Iye 1998.…”
supporting
confidence: 92%
“…Recently a growing amount of observational data has begun to confirm the reality of such structures, in particular in the centers of normal spiral galaxies. The most famous lopsided circumnuclear stellar disk belongs to M 31: its two brightness centers, one with high stellar velocity dispersion and the other dynamically cold, have been explained by Tremaine (1995) as an eccentric Keplerian disk around a supermassive black hole, and Bacon et al (2001) have argued that this disk must precess with an angular velocity of some 3 km s −1 pc −1 so suffering an m = 1 mode. In NGC 5055 there are too many asymmetries along the major axis: the brightness asymmetry, including [N II] and Hα emission lines, the rotation and stellar velocity dispersion asymmetries, and finally, the Mgb index distribution asymmetry found by us in this work.…”
Section: A Lopsided Circumnuclear Stellar Diskmentioning
confidence: 99%
“…The sketch of a model offered in Tremaine (1995) -for a lopsided Keplerian disc of stars around a MBH in the nucleus of M31 -has since been fleshed out in a number of numerical models (Statler 1999;Bacon et al 2001;Salow & Statler 2001;Sambhus & Sridhar 2002;Peiris & Tremaine 2003;Salow & Statler 2004;Kazandjian & Touma 2013;Brown & Magorrian 2013). This has brought to the forefront deep and interesting questions regarding the general nature of secular collisionless evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Schwarzschild-type methods have been used to construct non-axisymmetric equilibria, both kinematic (Peiris & Tremaine 2003) and self-consistent (Poon & Merritt 2001;Sambhus & Sridhar 2002;Brown & Magorrian 2013)). Early numerical simulations (Bacon et al 2001;Jacobs & Sellwood 2001) showed collisionless relaxation of perturbed stellar discs. Touma, Tremaine & Kazandjian (2009) built a numerical algorithm which is particularly suited to the numerical exploration of secular clusters.…”
Section: Introductionmentioning
confidence: 99%